2007
DOI: 10.1016/j.automatica.2006.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Kalman filtering with Markovian packet losses

Abstract: Abstract-We consider Kalman filtering in a network with packet losses, and use a two state Markov chain to describe the normal operating condition of packet delivery and transmission failure. We analyze the behavior of the estimation error covariance matrix and introduce the notion of peak covariance, which describes the upper envelope of the sequence of error covariance matrices {Pt, t ≥ 1} for the case of an unstable scalar model. We give sufficient conditions for the stability of the peak covariance process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
323
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(328 citation statements)
references
References 16 publications
5
323
0
Order By: Relevance
“…Bernoulli losses and showed that a critical value for the arrival rate exists such that the mean filtering error covariance is bounded for any arrival rate greater than that critical value. The stability analysis of Kalman filtering with binary Markovian packet losses can be found in [13,14] where the notion of peak covariance stability was first introduced in [15]. It is noticed in [13,15] that the given sufficient condition for the peak covariance stability involves an estimation of an upper bound of the solution of standard Riccati recursion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bernoulli losses and showed that a critical value for the arrival rate exists such that the mean filtering error covariance is bounded for any arrival rate greater than that critical value. The stability analysis of Kalman filtering with binary Markovian packet losses can be found in [13,14] where the notion of peak covariance stability was first introduced in [15]. It is noticed in [13,15] that the given sufficient condition for the peak covariance stability involves an estimation of an upper bound of the solution of standard Riccati recursion.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the stability studied in [13,14,15] is in fact in terms of mean filtering error covariance, and thus the term -peak covariance stability in the mean sense would be more precise. We still use peak covariance stability here for the consistency of the present paper with the aforementioned ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, what we consider is their homogeneous parts (32) and (33). Clearly, in the homogeneous parts there is no process noise ω k and the estimation error e s k is set to be zero as well, which is equivalent to setting their covariances to be zeros, that is, Q = S k = 0.…”
Section: Proof Of Part (I)mentioning
confidence: 99%
“…Its stability was studied in the pioneering work [25] where it is pointed out that there exists a critical value which determines the boundedness of the expected estimation error covariance (EEC), i.e., E[P k ]. Following [25], various aspects have been further researched, including the bound for the critical value [32], the distribution for EEC [27,28], the Markov packet losses case [26,[33][34][35]. In [29,30], the authors pointed out that P({P k ≤ M }) is a better evaluation for the estimation performance than the quantity E[P k ], and then obtained the lower and upper bounds for P({P k ≤ M }).…”
Section: B Related Work and Contributionsmentioning
confidence: 99%